SPEECH ACTS IN CORTEZ’S POLITICAL CAMPAIGN ADVERTISEMENT 2018 - Alima Nur Rosyida; Erfan Muhamad Fauzi (PROJECT (Professional Journal of English Education), 2020)
The study explores the role of language in the communication and interpretation of intentions by analyzing the narration of Alexandria Ocasio-Cortez’s political advertisement in Congressional Campaign in 2018. Hence, the study focuses on the pragmatic functions of locution, illocutionary and perlocutionary acts of the speeches. This study was conducted using the qualitative descriptive method. The findings show that the overall relative frequency percentages for the speech acts in Ocasio-Cortez’s 2018 political advertisement are: assertive 68%, directive 23%, commissive 4.5%, and declarative 4.5%. The results reflects that Ocasio-Cortez relied more on sentences that performed assertive acts than other speech acts since she wanted to introduce to the public who she is as an individual and what she is capable of as a future representative, and she also offered some relatable facts and situations that can appeal to the working class public to show that she’s on their sides. Using directive acts, she included herself as a part of the society and shows that she wants to make a change together with them, not on her own. This is a different approach to political advertisement since most of them rely more on the commissive acts by promising a better future for the society. This different strategy is something fresh that eventually played a part in her win in the 2018 Congressional District Election.Keywords:speech acts theory; pragmatics; political discourse; language and politics; political language.